The politics of oligarchy institutional choice in imperial Japan - Ramseyer, J. Mark; Rosenbluth, Frances McCall 1958- (Univ. Press, 1995)
In The Politics of Oligarchy, J. Mark Ramseyer and Frances M. Rosenbluth examine a key question of modern Japanese politics: Why were the Meiji oligarchs unable to design institutions capable of protecting their power? Using an analytical framework for oligarchic governments not specific to Japan, the authors ask why the oligarchs chose the political institutions they did, and what consequences those choices engendered for Japan's political competition, economic development, and diplomatic relations. Ramseyer and Rosenbluth argue that understanding these shifts in power may clarify the general dynamics of oligarchic government, as well as theoretical aspects of the relationship between institutional structure and regime change
Keywords: Geschichte 1868-1940; Bureaucratie - Japon - Histoire; Burocracia; Chemins de fer - Politique gouvernementale - Japon - Histoire; Estradas de ferro (aspectos economicos); Financas; Finances - Politique gouvernementale - Japon - Histoire; Oligarchie; Tissus de coton - Industrie - Politique gouvernementale - Japon - Histoire; Geschichte; Politik; Bureaucracy -- Japan -- History; Cotton textile industry -- Government policy -- Japan -- History; Finance -- Government policy -- Japan -- History; Railroads and state -- Japan -- History; Finanzpolitik; Wirtschaftspolitik; Politische Führung; Japon - Politique et gouvernement - 1868-; Japan -- Politics and government -- 1868-; Japan